Translocation of probiotics via gut–lung axis enhanced pulmonary immunity of weaned piglets exposed to low concentrations of ammonia - Jiajun Yang; Jing Wang; Peng Shang; Zongliang Liu; Bo Zhang; Dongsheng Yang; Hao Zhang (Ecotoxicology and Environmental Safety)
Objective: Lactobacillus salivarius is a probiotic bacteria strain in human and animal diets. The administration of probiotics to weaned piglets may improve their growth by optimizing the gastrointestinal bacterial composition. To further investigate the effect of bacterial communication between the gastrointestinal tract and lungs on bodily immunity, we reared weaned piglets in a low-ammonia gas environment. L. salivarius was supplemented to explore its effects on pulmonary immunity and its potential for bacterial translocation. Results: One hundred sixty weaned piglets were allocated to four groups: L. salivarius-supplemented, L. reuteri-supplemented, control, and antibiotic drug (aureomycin)-supplemented. The feeding duration was 28 d. The body weights of piglets administered a strain of Lactobacillus were better than those of the control (P < 0.01). The transcription level of immune factors interleukin 2 (IL-2), IL-4, interferon α (IFN-α), and tumor necrosis factor α (TNF-α) in cells of the ileum and lung was significantly higher (P < 0.01). Lung and ileal mucus tissues were isolated to sequence the bacterial composition, which suggested a higher richness in the lungs at the phylum level, which was not significant in the ileum. Functional bacteria were more abundant in the ileum and lungs. The proportion of the genera of Lactobacillus, Prevotella, Actinobacillus, and Prevotellaceae_ NK3B31_group increased in two tissues, and a lower ratio of Streptococcus, Escherichia-Shigella, and mycoplasma was detected. The correlation between the microbial genus composition and the levels of immune factors suggests that the abundance of Lactobacillus plays the same positive role in the lungs and ileum. Mycoplasmas play a negative role in ileal and pulmonary immunity. More Lactobacillus reuteri and anaerobic probiotic bacteria were detected in the lungs. Conclusion: The colonization of Lactobacillus salivarius and Lactobacillus reuteri in the membrane of the ileum optimized the ileal microbial composition, enrolled other probiotic bacteria translating to the lung, improved the abundance of pulmonary microbiota, and enhanced immunity after exposure to low concentrations of ammonia.